Theoretical analysis of fatigue failure in mechanically fastened Fibre Metal Laminate joints containing multiple cracks. (September 2018) - Wang, Wandong; Rans, Calvin; Benedictus, Rinze
Abstract: Mechanically fastened joints are susceptible to the presence of multiple-site damage (MSD) cracks in the critical fastener row. Different from the MSD growth in joints consisting of metallic substrates, the two coupled metal crack growth and interfacial delamination propagation failure mechanisms in Fibre Metal Laminates (FMLs) make the prediction of fatigue behaviour in FML joints with MSD scenario burdensome and impractical when considering all factors influencing the fatigue performance. This paper presents a theoretical study on the MSD crack growth behaviour in mechanically fastened FML joints with a focus of modelling the effects of bearing and bypass loads. The proposed model in this paper is built upon analytical models dealing with MSD growth in flat FML panels and single crack growth in FML panels subjected to a combined tension-pin loading case. This model would be particularly useful for symmetric FML joints where no secondary bending effects present. A deliberately designed symmetric FML joint was tested to validate the proposed model. The model captures the rapid crack growth in the vicinity of fastener holes due to bearing stresses and crack acceleration due to the interaction of cracks. It is identified that the load redistribution between intact fastener rows and the cracked fastener row accelerates crack growth with crack length. The effects of secondary bending stresses in FML joints on the crack growth behaviour is extensively discussed. The performance of the proposed model for single lap FML joints is also examined using test data from open literature. It is found that the proposed model provides a conservative prediction for the tested single shear lap FML joint from open literature. Highlights: Both pin bearing and MSD crack interaction accelerate the crack growth rate in FML joints. Load redistribution among fastener rows accelerate the crack growth in the cracked fastener row. The proposed model is particularly useful for symmetrically and mechanically fastened FML joints.